Geotechnics for Natural and Engineered Sustainable Technologies GeoNEst - Krishna, A. Murali; Dey, Arindam; Sreedeep, S. (Developments in Geotechnical Engineering,, 2018)
This contributed volume encompasses contributions by eminent researchers in the field of geotechnical engineering. The chapters of this book are based on the keynote and sub-theme lectures delivered at the Indian Geotechnical Conference 2017. The book provides a comprehensive overview of the current state-of-the-art research and practices in different domains of geotechnical engineering in the areas of soil dynamics, earth retaining structures, ground improvement, and geotechnical and geophysical investigations. It will serve as an ideal resource for academics, researchers, practicing professionals, and students alike. .